Penyelenggara Dana Perlindungan Pemodal Bagi Investor Dalam Transaksi Saham Pada Pasar Modal - Mohammad Solehodin Attijani (Universitas Airlangga, 2019)
AbstractInvestors who want to invest in the capital market in Indonesia, which include securities in the form of shares, need to have a good knowledge of investment objects because basically all investments contain risk and there is no guarantee of getting profits. Investor protection fund operators have the main goal of forming investor protection funds to increase protection and trust that investors’ assets are safe without being worried about the inability of securities companies to fulfill their obligations. The capital market can fail due to loss of investor distrust caused by the failure or bankruptcy of securities companies, resulting in a systemic effect that can reduce the reliability of the capital market industry. Through the organizer of the protection fund investors will provide compensation claims to investors who are victims of violations and securities crimes, not from loss of personal transactions. Investors whose assets receive investor protection funds are investors who meet the requirements set by the financial services authority.Keywords : Organizers of Investor Protection Funds, Investor Compensation Claims AbstrakInvestor yang ingin berinvestasi pada pasar modal di Indonesia, yakni antara lain surat berharga berbentuk saham, perlu memiliki pengetahuan yang baik mengenai obyek investasi karena pada dasarnya semua investasi mengandung risiko dan tidak ada jaminan pasti mendapatkan keuntungan. Penyelenggara dana perlindungan pemodal mempunyai tujuan utama membentuk dana perlindungan pemodal untuk meningkatkan perlindungan dan kepercayaan bahwa aset investor aman tanpa dihinggapi rasa khawatir atas ketidakmampuan perusahaan efek dalam memenuhi kewajibannya. Pasar modal dapat mengalami kegagalan akibat hilangnya ketidakpercayaan pemodal yang disebabkan kegagalan atau kebangkrutan perusahaan efek, sehingga menimbulkan efek sistemik yang dapat menjatuhkan kridibilitas industri pasar modal. Melalui penyelenggara dana perlindungan pemodal akan memberikan klaim ganti rugi kepada investor yang menjadi korban dari pelanggaran dan kejahatan sekuritas, bukan dari kerugian transaksi pribadi. Investor yang asetnya mendapat dana perlindungan pemodal adalah investor yang memenuhi persyaratan yang telah ditentukan otoritas jasa keuangan.Kata Kunci : Penyelenggara Dana Perlindungan Pemodal, Klaim Ganti Rugi Investor